THEORETICAL-METHODOLOGICAL ANALYSIS OF THE PROBLEM OF POST-TRAUMATIC GROWTH OF FAMILY MEMBERS IN THE CONDITIONS OF WAR (Psychology Travelogs, 2024)
In the article, a theoretical and methodological analysis of the current state of the development of the problem of posttraumatic growth in family members during wartime has been conducted. The fundamental models of growth—functional-descriptive, person-centered, biopsychosocial, and psychological-philosophical—are reviewed.Key concepts related to this issue have been highlighted: social support, personal activity, assimilation and accommodation, consequences, and variables of traumatization. The role of the social environment of the family for potential growth, which is considered a desirable scenario of development after trauma, is emphasized. Attention is focused on the role of support, empathy, communication, mutual aid, "listening," expectations, and the peculiarities of family life.As a result of the theoretical analysis, the main trends of modern families during wartime and the difficulties they face have been identified. Among them are issues with the implementation of the family's material and psychological (protective) functions; disruption of the family's adaptation mechanism to crisis events (war, forced migration); changes and contradictions in family roles; complications in parent-child relationships; instability of plans during wartime; and the impact of pathogenic factors on the mental health of family members. The works addressing the features of emotional reactions and components of posttraumatic growth in different age groups—children, adolescents, and adults—have been analyzed. Changes in the value-semantic sphere, particularly the awareness of the value of life because of the war, are emphasized. It is illustrated that changing attitudes toward the traumatic event or increasing self-attention are important processes and strategies to facilitate growth.Some domestic empirical studies concerning posttraumatic growth and methodological developments have also been analyzed. The problems of adapting methodological tools are outlined. Prospects for further research are analyzed.
Keywords: posttraumatic growth; war; family; theoretical model; social environment; support; family relationships